1967
DOI: 10.1002/jlac.19677040116
|View full text |Cite
|
Sign up to set email alerts
|

Naphthotriazine, I. Synthese N‐substituierter peri‐Naphthotriazine

Abstract: Interessante Unterschiede im spektralen und chemischen Verhalten der beiden Methylisomeren z), die unseres Wissens keine Parallele in der Benzotriazolreihe finden, veranlaBten uns, eine groljere Zahl weiterer noch nicht beschriebener Isomerenpaare herzustellen und ihre Eigenschaften zu vergleichen.a: it1 = IP 1 it3 = 11; it' = . \ l k y l , -\r?i b: li' = It2 = C l I a , It3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1967
1967
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…It is well established that when the conjugate base of 1H-naphtho[1,8-de]-1,2,3,-triazine is alkylated with dimethyl sulfate a mixture of 1-and 2methylnaphtho[1,8-de]-1,2,3,-triazine, 2 and 3 results (Scheme 2). [18][19][20][21][22] Although the return of heterocycles from this methylation is good (70 %), the regioselectivity is poor and the mixture is close to 1:1 in the two isomers. The two isomers 2 and 3 are however readily separated and purified by column chromatography on silica gel.…”
Section: Resultsmentioning
confidence: 99%
“…It is well established that when the conjugate base of 1H-naphtho[1,8-de]-1,2,3,-triazine is alkylated with dimethyl sulfate a mixture of 1-and 2methylnaphtho[1,8-de]-1,2,3,-triazine, 2 and 3 results (Scheme 2). [18][19][20][21][22] Although the return of heterocycles from this methylation is good (70 %), the regioselectivity is poor and the mixture is close to 1:1 in the two isomers. The two isomers 2 and 3 are however readily separated and purified by column chromatography on silica gel.…”
Section: Resultsmentioning
confidence: 99%
“…(3), which is obtained in 96.5 % yield from (2) While investigating the temperature dependence of formation of the benzene radical anion in T H F / D M E with liquid K/Na alloy, we observed that the ESR septet found at low temperatures (below about -2OOC) (Fig. 1) gives way on warming t o a new spectrum (Fig.…”
mentioning
confidence: 80%
“…It follows that (3) and (4) are formed from (2) by stepwise addition of electrons to the iron-phthalocyanine complex. If we include FePcC1, which has been described by Barrett et al [51, and whose structure as iron(111) phthalocyanine chloride we finally proved I61, we now know six iron-phthalocyanine complexes of differing total electron numbers.…”
Section: Bm [4]mentioning
confidence: 99%
“…), Amax (in methanol) = 503, 332, 318, 306, 227 m p with log E = 3.1 3, 3.86, 3.85, 3.77, 4.89. The structure of (3) follows from the bathochromic shift of the longest wavelength band in comparison with (2) Benzene radical anions, C6H6-, are obtained on reduction of benzene with alkali metals in solvent systems which dissolve the metals with formation of solvated electrons (e.g. tetra-…”
Section: Bm [4]mentioning
confidence: 99%